Development of a Zebrafish embryo‐based test system for thyroid hormone system disruption: 3Rs in ecotoxicological research - Gölz, Lisa; Blanc-Legendre, Melanie; Rinderknecht, Maximilian; Behnstedt, Laura; Coordes, Sara; Reger, Luisa; Sire, Sacha; Cousin, Xavier; Braunbeck, Thomas; Baumann, Lisa (Environmental toxicology and chemistry, 2024)
There is increasing concern regarding pollutants disrupting the vertebrate thyroid hormone (TH) system, which is crucial for development. Thus, identification of TH system-disrupting chemicals (THSDCs) is an important requirement in the Organisation for Economic Co-operation and Development (OECD) testing framework. The current OECD approach uses different model organisms for different endocrine modalities, leading to a high number of animal tests. Alternative models compatible with the 3Rs (replacement, reduction, refinement) principle are required. Zebrafish embryos, not protected by current European Union animal welfare legislation, represent a promising model. Studies show that zebrafish swim bladder inflation and eye development are affected by THSDCs, and the respective adverse outcome pathways (AOPs) have been established. The present study compared effects of four THSDCs with distinct molecular modes of action: Propylthiouracil (PTU), potassium perchlorate, iopanoic acid, and the TH triiodothyronine (T3) were tested with a protocol based on the OECD fish embryo toxicity test (FET). Effects were analyzed according to the AOP concept from molecular over morphological to behavioral levels: Analysis of thyroid- and eye-related gene expression revealed significant effects after PTU and T3 exposure. All substances caused changes in thyroid follicle morphology of a transgenic zebrafish line expressing fluorescence in thyrocytes. Impaired eye development and swimming activity were observed in all treatments, supporting the hypothesis that THSDCs cause adverse population-relevant changes. Findings thus confirm that the FET can be amended by TH system-related endpoints into an integrated protocol comprising molecular, morphological, and behavioral endpoints for environmental risk assessment of potential endocrine disruptors, which is compatible with the 3Rs principle. Environ Toxicol Chem 2024;00:1-18. © 2024 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.
First published: 28 May 2024
Gesehen am 11.06.2025